Expanded Tumor-infiltrating Lymphocytes From Soft Tissue Sarcoma Have Tumor-specific Function. Issue 2 (February 2021) - Mullinax, John E.; Hall, MacLean; Beatty, Matthew; Weber, Amy M.; Sannasardo, Zachary; Svrdlin, Tanja; Hensel, Jonathan; Bui, Marilyn; Richards, Allison; Gonzalez, Ricardo J.; Cox, Cheryl A.; Kelley, Linda; et al.
Abstract : Adoptive cell transfer (ACT) with tumor-infiltrating lymphocytes (TILs) can generate durable clinical responses in patients with metastatic melanoma and ongoing trials are evaluating efficacy in other advanced solid tumors. The aim of this study was to develop methods for the expansion of tumor-reactive TIL from resected soft tissue sarcoma to a degree required for the ACT. From 2015 to 2018, 70 patients were consented to an institutional review board–approved protocol, and fresh surgical specimens were taken directly from the operating room to the laboratory. Fragments of the tumor (1 mm 3 ) or fresh tumor digest were placed in culture for a period of 4 weeks. Successfully propagated TIL from these cultures were collected and analyzed by flow cytometry. TIL were cocultured with autologous tumor and function was assessed by measurement of interferon-γ in the supernatant by enzyme-linked immunosorbent assay. Initial TIL cultures were further expanded using a rapid expansion protocol. Nearly all specimens generated an initial TIL culture (91% fragment method, 100% digest method). The phenotype of the TIL indicated a predominant CD3 + population after culture (43% fragment, 52% digest) and TIL were responsive to the autologous tumor (56% fragment, 40% digest). The cultured TIL expanded to a degree required for clinical use following rapid expansion protocol (median: 490-fold fragment, 403-fold digest). The data demonstrate the feasibility of TIL culture from fresh soft tissue sarcoma. The derived TIL have tumor-specific reactivity and can be expanded to clinically relevant numbers. An active ACT clinical trial using the methods described in this report is now approved for patients with metastatic soft tissue sarcoma.